Hepatitis B Virus Infection in Blood Donors - Salma Ghulam Nabi Amna Faruqi , Syed Imran Ahmad , Syed Tousif Ahmed (Journal of Rawalpindi Medical College, 2014)
Background: To find out the frequency of hepatitis B virus (HBV) infection in blood donors and to analyze it’s trend over a five year period in Pakistan. Methods: In this retrospective and descriptive study screening of all blood donors was done to separate healthy donors from unhealthy donors by a questionnaire and blood complete picture. Apparently healthy subjects of 18 years or more with a hemoglobin level of twelve or more were allowed to donate blood. Sera were checked for the presence of hepatitis B surface antigen (HBsAg). Results: A total of 246,611 patients blood were screened during the five years of our study. The frequency of HBV was 1.63%. The overall frequency of HBV showed a statically significant decreasing trend over the five years of our study. Conclusion: The decreasing trend in the frequency of HBV in blood donors is a positive aspect and should be further sustained.